Romanian Constitutional Identity in Historical Context - Guțan, Manuel (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
This paper is approaching the Romanian constitutional identity as a tendential constitutional identity. This concept emphasizes a perpetual competition between two historical Romanian identity poles: a eurocentric and an etnocentric one. From the nineteenth century, the Romanians constantly desired to obtain a full European constitutional identity but they always feared to give in their constitutional ethnocentric identity.This is why the Romanian constitutional identity was and still is nothing but a neverending tendency towards constitutional Europeanization. Due to its dynamic character, the Romanian constitutional identity was closer either to its eurocentric pole or its ethnocentric one. Sometime it had a democratic-liberal European look, some other time it had a strong illiberal look.KEYWORDS: Romanian constitutionalism, tendential constitutional identity, bipolar constitutional identity, eurocentric constitutional identity, ethnocentric constitutional identity.